IMPLEMENTASI TUGAS DAN WEWENANG PENYIDIK TERHADAP PERLINDUNGAN PENYU HIJAU - Prasetyo, Budi (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 3 No 3 (2014)DO - 10.24843/JMHU.2014.v03.i03.p10, 2014)
The research of officer task and authority implementation towards green turtle conservation (study case of Marine Police Directorate Regional Bali) aims to describing and analizing officer task and authority implementation in deep based on both KUHAP or Conservation Law. Besides, this research also aims to figure out the enabling and inhibiting factors in implementing officer task and authority towards green turtle conservation, also researching the steps taken by of Marine Police Directorate Regional Bali. The need for green turtle in Bali is rising up to this time. Although many criminal offensers got caught by of Marine Police Directorate Regional Bali officers but it is still going on. Based on this situation, a question arises how is the implementation of officer task and authority towards green turtle conservation and what are the enabling and inhibiting factors. The method used in this research is empirical legal research with descriptive research using prime and secondary data resouces with interview and also related available documents. This research uses non probability sampling technique which is purpose sampling with quota sampling that is a process of sample withdrawing by observing the easiest sample to take and the sample has special features that attracts the researcher. With all collected data, managed using qualitative analysis and the data presented descriptively and sistematically. Based on the research done before, it is noticed that the implementation of officer task and authority towards green turtle conservation based on KUHAP and Conservation Law has been going well. Granting rights for the suspects of green turtle trading during the investigation has been done by the officers based on KUHAP. The factors which becomes the enabling task for officer task and authority towards green turtle is the law factor, law enforcement, equipment and facilities, and culture. Meanwhile the society factor is the main inhibiting factor for implementing officer task and authority towards green turtle conservation. The habit of consuming turtle meat and guise of religious ceremony are mostly used as the reasons in trading this protected animal.
Keywords: implementation, officer task and authority, green turtle conservation